2022
DOI: 10.1111/1756-185x.14295
|View full text |Cite
|
Sign up to set email alerts
|

The burden of illness of rheumatoid arthritis in Latin America—A systematic literature review

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by inflammation and progressive destruction of joints. 1 Over 23 million people worldwide suffer from RA. The disease has variable expression and outcome ranging from mild, limited disease to severe disease associated with progressive joint destruction and reduced survival. 1 Substantial comorbidity can be seen outside the musculoskeletal system, with excess cardiovascular risk, dyslipidemia, and propensity for infection partially related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…The pathogenesis of rheumatoid arthritis (RA) involves genetic background, obesity ( 12 ), chronic infection ( 13 ), and environmental factors such as oral hygiene ( 14 ), smoking ( 15 ), and diet ( 16 ), which can influence oral ( 17 ) and gut microbiota ( 18 ) and thus indirectly impact the development of RA. Take obesity as an example, as shown in a US study ( 12 ) and other studies ( 19 , 20 ), it accounts for 4.8 cases per 100,000 (52%) of the increased incidence of female RA patients between 1985 and 2007. As mentioned above, tight control of blood sugar with sulfonylureas or biguanides is beneficial to several DM-related endpoints ( 11 , 21 ), which confers the similarity in the pathogenesis between the RA and DM ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 86%
“…The pathogenesis of rheumatoid arthritis (RA) involves genetic background, obesity ( 12 ), chronic infection ( 13 ), and environmental factors such as oral hygiene ( 14 ), smoking ( 15 ), and diet ( 16 ), which can influence oral ( 17 ) and gut microbiota ( 18 ) and thus indirectly impact the development of RA. Take obesity as an example, as shown in a US study ( 12 ) and other studies ( 19 , 20 ), it accounts for 4.8 cases per 100,000 (52%) of the increased incidence of female RA patients between 1985 and 2007. As mentioned above, tight control of blood sugar with sulfonylureas or biguanides is beneficial to several DM-related endpoints ( 11 , 21 ), which confers the similarity in the pathogenesis between the RA and DM ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 86%
“…Compared with the rest of the world (RoW), LATAM patients with RA show a higher ratio of females to males (5.2:1 vs 3:1), an earlier age of onset, and a poorer prognosis due to genetic and epidemiologic differences [ 2 – 5 ]. In the RoW, RA accounts for 0.13% of world disability-adjusted life years; in a study investigating RA in five LATAM countries (Brazil, Colombia, Venezuela, Argentina, and Mexico), it was found that these figures are higher in the LATAM population (0.16%, 0.21%, 0.24%, 0.16%, and 0.30%, respectively), indicating a higher burden of disease [ 6 ]. This may result from challenges in the management of RA in LATAM countries, such as delays in referral, limited resources, and lack of education, as well as a relatively high prevalence of infectious diseases such as tuberculosis (TB) and malaria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The drug has been used to treat malaria endemic in eighteen countries in Latin America and the Caribbean and has seen an increase in estimated case incidence since 2015, where Brazil represents 20% of cases (WHO, 2020). Chloroquine has also been used for rheumatoid arthritis and lupus erythematosus (Rainsford et al, 2015), non-endemic diseases that have also registered an increase in this region (Hernández-Negrín and Padilla-Cueto, 2020; Papadimitropoulos et al, 2022). In recent decades its action has been explored as a broad-spectrum antiviral agent in inhibiting the replication of other respiratory viruses, such as influenza A/H5N1, SARS-CoV, and human coronavirus 229E (Savarino et al, 2003;Vincent et al, 2005;Kono et al, 2008;Murray et al, 2010;Yan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%